A systematic review of the use of acceptance and commitment therapy in supporting parents. (13th May 2020) - Byrne, Gary; Ghráda, Áine Ní; O'Mahony, Teresa; Brennan, Emma
Abstract : Objectives: Acceptance and commitment therapy (ACT) has accrued a growing evidence‐base for a wide variety of psychological difficulties. Given that ACT promotes broad and flexible repertoires of behaviour as well as neutralizing the ubiquitous psychological processes theorized to be responsible for much human suffering, such an approach may hold promise. The use of ACT‐informed parenting interventions offers another alternative to solely behavioural approaches but it remains relatively understudied and in need of further exploration. Design: The current systematic review, which searched four databases, aimed to collate all ACT interventions that included parental therapeutic components in the treatment of various child presenting difficulties. The review also rated the methodological rigour of the ACT evidence‐base for this type of treatment format. Results: Twenty‐seven individual studies covering a broad spectrum of presenting problems were included, comprising of 1, 155 participants. A large proportion of studies were within‐group designs with a smaller number using randomized controlled trials. The majority of studies reported improvements on either parent report symptoms regarding child physical or psychological functioning as well as parent‐reported measures of stress, depression, and anxiety. Similar improvements were noted on a number of ACT mechanisms of change outcomes, including mindfulness, acceptance, and cognitive fusing. These gains were evident for parents of children with neurodevelopmental disorders, chronic pain, and significant physical health difficulties. Maintenance or further treatment gains were often reported at follow‐up. These positive findings are tempered by low levels of methodological rigour common in some of the studies included. Conclusions: Despite these limitations, ACT holds promise as a transdiagnostic intervention that can help with the parenting of children with a range of psychological and physical difficulties. Practitioner points: ACT has accrued a relatively strong evidence base for a range of psychological difficulties. Despite some methodological shortcomings, ACT shows promise as an intervention to help parents manage stress and difficulties especially in relation to children with autism, chronic pain, and physical health needs. Further research is required in comparing ACT to more established treatments and helping consolidate initial positive findings.